1986
DOI: 10.1021/bi00371a066
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of some macrolide antibiotics with the ribosome. Labeling of the binding site components

Abstract: Radioactive carbomycin A, niddamycin, tylosin, and spiramycin, but not erythromycin, can be covalently bound to Escherichia coli ribosomes by incubation at 37 degrees C. The incorporation of radioactivity into the particles is inhibited by SH- and activated double bond containing compounds but not by amino groups, suggesting that the reactions may take place by addition to the double bond present in the reactive antibiotics. This thermic reaction must be different from the photoreaction described for some of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
13
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 39 publications
3
13
0
Order By: Relevance
“…Post-translocation complex of poly(U)-programmed ribosomes, complex C, carrying tRNA Phe and Ac[ 3 H]Phe-tRNA at the E-and P-sites, respectively, was prepared in buffer A (100 mM Tris/HCl, pH 7.2, 4.5 mM Mg(CH 3 COO) 2 , 150 mM NH 4 Cl, and 6 mM 2-mercaptoethanol) and purified according to Dinos et al (31). Whenever required, 100 M spermine or a mixture of 50 M spermine and 2 mM spermidine was also included in buffer A.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Post-translocation complex of poly(U)-programmed ribosomes, complex C, carrying tRNA Phe and Ac[ 3 H]Phe-tRNA at the E-and P-sites, respectively, was prepared in buffer A (100 mM Tris/HCl, pH 7.2, 4.5 mM Mg(CH 3 COO) 2 , 150 mM NH 4 Cl, and 6 mM 2-mercaptoethanol) and purified according to Dinos et al (31). Whenever required, 100 M spermine or a mixture of 50 M spermine and 2 mM spermidine was also included in buffer A.…”
Section: Methodsmentioning
confidence: 99%
“…Binding of Antibiotics and Probing of Complexes-Complex C at 100 nM was incubated alone or with antibiotics (I) at concentration equal to 50 ϫ K i in 100 l of buffer B (HEPES-KOH, pH 7.2, 4.5 mM Mg(CH 3 COO) 2 , 150 mM NH 4 Cl, 5 mM dithiothreitol) at 25°C, either for 10 s or for 8 ϫ t1 ⁄ 2 min, dependent on whether the encounter complex CI or the final complex C*I was desired to be probed, respectively. The term t1 ⁄2 , which represents the half-life for the attainment of equilibrium between complex C and the drug, was calculated through the relationship,…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, immuno electron microscopic studies indicated that the proteins listed above are scattered over a large fraction of the ribosome surface (6) and clearly cannot all be in the vicinity of the tRNA 3' terminus. The diversity of proteins labeled no doubt derives, at least in part, from the size of the reactive substituents, as the crosslinks they establish are typically [10][11][12][13][14][15][16][17][18][19][20] A in length and may therefore extend to ribosomal components at a considerable distance from the site of tRNA binding.…”
mentioning
confidence: 99%